Postprandial duodenal function in man. Issue 8 (August 1978) - Miller, L J; Malagelada, J R; Go, V L
Abstract : Duodenal function was studied in 11 healthy volunteers after intragastric instillation of a mixed semi-elemental meal. The duodenum accepted chyme of varying pH, osmolality, and nutrient concentration; and, as a result of biliary, pancreatic, and enteric secretion as well as absorption, it delivered chyme with nearly constant pH, osmolality, and nutrient concentration to the jejunum. The flow rate and nutrient load of jejunal chyme varied. The duodenum absorbed more carbohydrate than lipid and less protein, taking up each nutrient at a constant rate during most of the postprandial period. The percentage of nutrient load absorbed was greatest in the late postprandial period, when flow rate, nutrient load, and concentrations were low.